Penerapan Model Numbered Head Together Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Ayunda, Desi Sary; Muhammad; Liani, Novi Sari (Jurnal Aktual Pendidikan Indonesia, 2022)
The teacher is very influential in the teaching and learning process, the success achieved by students is inseparable from the role of the teacher. Therefore, the purpose of this study is to describe how the application of the numbered head together (NHT) model can improve student motivation and learning outcomes. The research method used is classroom action research. This research was conducted by means of pre-cycle, first cycle and second cycle. The results showed that in the first cycle there was an increase where 14 students got scores above the average or according to the KKM target but 16 students still got scores below the KKM, which is 75 established national completeness. The average value in this cycle is 68 with the highest value of 80 and the lowest value of 35. However, at this stage it has increased even though it is not significant. the second cycle experienced an increase that was more than in the first cycle, to listen/pay attention to information there were 27%, students were very serious about listening to the teacher's explanations, students/groups were active in asking questions 90%. And the average value of students also increased as high as 85% so that many students reached the KKM value that had been set, and students were very enthusiastic during the learning process.